2010
DOI: 10.1007/s12289-010-0989-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the strain-path dependency of stress-based forming limit curves

Abstract: Path-dependent forming limits have been computed for sheet metals undergoing various combinations of plane stress loading conditions. This paper presents a theoretical model for prediction of stress-based forming limit curves (SFLC) based on the Marciniak and Kuczynski (MK) model. Acceptable agreement was observed between calculated forming limit curves (FLC) and experimental data for AISI-1012 steel (Molaei 1999) and AA-2008-T4 alloys (Graf and Hosford Metallurgical Trans 24A:2503-2512, 1993. In this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…In case of M-K model, requirement is least and only one point of experimental FLD (usually FLD 0 (FLD 0 is the major strain in plane strain state that results in necking)) is needed to find the initial in-homogeneity coefficient, f 0 , and calibrate the diagram. [31][32][33][34][35] As reported in the literature, 34,35 sensitivity of the diagram to variations of f 0 is very high and if it is presumed inaccurately, the resulting FLD will differ greatly from the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…In case of M-K model, requirement is least and only one point of experimental FLD (usually FLD 0 (FLD 0 is the major strain in plane strain state that results in necking)) is needed to find the initial in-homogeneity coefficient, f 0 , and calibrate the diagram. [31][32][33][34][35] As reported in the literature, 34,35 sensitivity of the diagram to variations of f 0 is very high and if it is presumed inaccurately, the resulting FLD will differ greatly from the experimental data.…”
Section: Resultsmentioning
confidence: 99%
“…The FLD is widely accepted as an efficient tool to analyze the formability of sheet metals. [11][12][13][14][15][16][17][18][19][20][21][22][23][24]…”
Section: Introductionmentioning
confidence: 99%
“…Forming limit curves (FLCs) are applied to determine the sheet metals formability. The laboratory tests results has demonstrated that the FLCs are effected by several factors containing strain rate [5,6], strain hardening index and anisotropy coefficients [7,8], heat treatment [9,10], grain size and microstructure [11], strain path changes [12][13][14] and sheet thickness [15][16][17].…”
Section: Introductionmentioning
confidence: 99%